Internalisasi Nilai-Nilai Moderasi Beragama dalam Pelaksanaan Pembelajaran Akidah Akhlak di Madrasah - Fitriyah Fitriyah; Abdul Hadi; Muhammad Hambal Shafwan (Dinasti Review, 2024)
Indonesia, with its diversity, is seen as an unavoidable gift from the Creator. As a country rich in culture and natural resources, Indonesia offers a colorful palette of life, where each of its citizens has diverse views, beliefs, and interests, including in religion. This diversity can still be bridged by the use of Indonesian as the national language. This study, which uses a qualitative approach through interviews, observations, and documentation, explores how the internalization of religious moderation values is carried out in Madrasah Aliyah. This process includes value transformation in learning and cultum, value transaction through interactive methods such as questions and answers, stories, parables, and advice supported by counselling guidance, and value internalization, where values are taught to be applied in daily life, such as accepting differences, acting fairly, and respecting rules. Textbooks, muhadharah activities, teacher recitation, and habituation support this internalization, while the out-of-school environment and social media are noted as inhibitors.